2018
DOI: 10.1101/500041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genotyping-by-sequencing reveals the effects of riverscape, climate and interspecific introgression on the genetic diversity and local adaptation of the endangered Mexican golden trout (Oncorhynchus chrysogaster)

Abstract: AbstractHow environmental and anthropogenic factors influence genetic variation and local adaptation is a central issue in evolutionary biology. The Mexican golden trout (Oncorhynchus chrysogaster), one of the southernmost native salmonid species in the world, is susceptible to climate change, habitat perturbations and the competition and hybridization with exotic rainbow trout (O. mykiss). The present study aimed for the fi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 119 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Studies have already pointed out that local adaptations may affect the genetic diversity of populations [53,54]. Research on Artemia have shown that some morphological features could differ signi cantly not only in different species [55], but also in different salt lakes with different hydrochemical characteristics [56,57], suggesting that Artemia populations could develop local adaptation and exhibit different adaptive characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have already pointed out that local adaptations may affect the genetic diversity of populations [53,54]. Research on Artemia have shown that some morphological features could differ signi cantly not only in different species [55], but also in different salt lakes with different hydrochemical characteristics [56,57], suggesting that Artemia populations could develop local adaptation and exhibit different adaptive characteristics.…”
Section: Discussionmentioning
confidence: 99%